A study on maintenance approach of historical buildings in Kuala Lumpur / Nur Fadhilah Bahardin - Bahardin, Nur Fadhilah (Faculty of Architecture, Planning and Surveying, 2008)
These past few years has seen that the historic outlook has changed due to the rapid development that takes its toll on the historical spaces and building. Realizing the importance of maintenance what once were the traces of the historical heritage in Malaysia, this dissertation which titled “A Study on Maintenance Approach of Historical Building in Kuala Lumpur” is documented. This research comprises of 6 chapters. This research intends to identify the maintenance approach that being applied in the historical building and the current level of maintenance works undertaken. In addition to this, site observation and inventory record was also undertaken to identify the location and condition of selected historical buildings. Case studies on twenty numbers of historical buildings that are located in Kuala Lumpur area were undertaken to highlight the background information of the building and the typology of the historical building in Kuala Lumpur; and all these information are documented in Chapter 3 and 4. Analysis for the research comprise of descriptive approach as well as statistical analysis which are based on questionnaire survey. The findings revealed that maintenance approach of historical building in Kuala Lumpur and the current maintenance level were gathered through structured questionnaire survey and the results were then critically analyzed. From the findings, hopes that the research would give clear perception to the reader on the maintenance approach and current maintenance practice of historical building that implement in Kuala Lumpur. Based on the findings of the research, it can be concluded that the standard of maintenance practice on historical buildings in Kuala Lumpur is still under development and there is a need to standardize and made detailed on the scope of maintenance works undertaken in order to ensure that comprehensive maintenance can be applied on those building to achieve the acceptable condition and remain the existing historical element. It is recommended that the involved parties could make more consideration to related aspect of public education, enforcement and specified laws and guidelines and also establishment of maintenance procedures and policy in a way to maintain the historical buildings. In addition to this, publish and promote efforts to maintain these historic building throughout the Kuala Lumpur as well as the whole country.